THE INFLUENCE OF INTERNAL CONTROL SYSTEMS, HUMAN RESOURCE COMPETENCE, AND USE OF INFORMATION TECHNOLOGY ON THE QUALITY OF FINANCIAL REPORTS - Searly Alviola; Yusuf Faisal; Lembah Dewi Andini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to determine the internal control system, human resource competence, and the use of information technology on the quality of financial reports. Respondents in this study totaled 150 respondents consisting of employees of PT. Vantsing International Group as many as 50 respondents and employees of PT. X as many as 100 respondents. Researchers use comparative causal research, to determine the influence of one or more independent variables on the dependent variable. Researchers used PLS SEM version 3.0 statistical software. The results of this research found that the internal control system has a positive and statistically significant effect on the quality of financial reports, as well as human resource competence has a positive and statistically significant effect on the quality of financial reports, and also the use of information technology has a positive and statistically significant effect on quality. financial statements. This research focuses on the quality of financial reports of a private company, where the majority of previous research has examined the quality of financial reports in the government environment.